An exploratory study on collaborative modes of professional development and learning for teachers of students with autism spectrum disorder (ASD). Issue 2 (21st September 2018) - Ho, Fuk Chuen; Lam, Cici Sze‐Ching; Sam, Sam Ka‐lam; Arthur‐Kelly, Michael
Abstract : This study aims to deliver a school‐based mode of training for in‐service teachers of students with ASD in Hong Kong. The training is delivered following the phases of implementation science, namely, exploration, installation, and implementation. The project team used the theory of mind approach, which enables teachers to engage with students with ASD and to focus on recognizing and reacting to emotions. Participants in this study included four educators from a teacher education institution, three expert teachers, and 19 in‐service teacher trainees. The most salient responses came from trainees who were provided with the opportunity to apply learned skills in their own classrooms immediately and to share the knowledge and skills in dealing with students with ASD in the post‐conference meetings.